Cybersecurity attacks (Red Team activity) - Nesterenko, Sergii (Packt, 2018)
"There is only way to become really good at cybersecurity: you must know both how to attack and how to defend. First of all, you have to learn to think like a hacker, so you deeply understand what the threats are. Then you'll need to know how to protect yourself from the attacks. We start with precise descriptions and examples of network attacks to show you how the malicious hackers can break into your network--and what harm they can do. Then we'll look at another attack vector: websites and web-applications. You'll see the most vulnerable places and understand what cybercriminals will do if they find them. Then we'll discover the third vector of attacks: humans. Refined hackers know how to hack a human brain first to hack digital assets. You'll find out what social engineering, phishing, and spear-phishings, and why they're becoming especially dangerous today. By the end of this course, you'll be able to locate all your vulnerabilities and remediate them before malicious hackers find and exploit them."--Resource description page